Strategi Adaptasi Migran Banjar Di Kota Palangka Raya (Pasca Konflik Dayak-Madura Kalimantan Tengah) = Adaptation Strategy of Banjarese Migrant in Palangka Raya (Post-Conflict between the Dayakese and Maduranese in Centr - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The conflict between the Dayakese and Maduranese in Central Kalimantan brought a deep impact to the existence of migrants in destination area. The Banjarese is one of the biggest ethnics in Palangka Raya that experience this conflict. Thus, it is important to do a research toward the Banjarese migrants on their efforts to reconstructs adaptation strategy in co lict areas to be able to survive. The aim of this research is to know the social condition of the Banjarese migrants, their adaptation strategy, and elements which influence it during the post-conflict phase in Palangka Raya. The research uses survey and individual analysis unit in Panarung and Pahandut villages. Data were collected based on purposive sampling with the sum of 40 people. The analysis technique were used statistic test. The data were completed by qualitative analysis through interpretation toward interview and field observation. The result shows: (1) The post-conflict phase has grown the Banjarese awareness to reconstruct adaptation strategy toward natives by social interaction reinforcement, involvement in social action and making use of voluntary association as an inter-ethnic social relationship net. The adaptation strategy is done based on the economic interest. (2) There is difference between the Banjarese migrants in Panarung and Pahandut in their adaptation strategy caused by age, kind of jobs, education level, duration of staying and location. The adaptation strategy in Panarung is better than in Pahandut, but adaptation strategy by making use of voluntary association in Pahandut is better than in Panarung (3) The level of crimes, the Banjarese involvements in politics and Islamic activities have raised new problems in inter-ethnic relationship. Transparency and tolerance are needed in seeing the existence of each ethnic group. Government needs to encourage social activities in order to support togetherness among ethnics in Palangka Raya.